DETERMINAN KEBIJAKAN HUTANG (DALAM AGENCY THEORY DAN PECKING ORDER THEORY) - Pancawati Hardiningsih; Rachmawati Meita Oktaviani (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2012)
The aims of this study is to analyze the impact of the variables free cash flow, Profitability,Growth, Tangibility, Retained Earning and Managerial Ownership on debt. Research usingpurposive sampling method for taking samples. Data obtained on the basis of the publication ofIndonesian Capital Market Directory (ICMD), Samples of this research is manufacturing firmwhich listed in Indonesian Stock Exchange during 2007-2011. This research obtained 135 samplesof manufacturing firms. Analysis technique used is multiple regression analysis. Based on the teststatistic F indicates that the model is fit because has a significance value less than 5% of Alphavalue. The Result of analisys show that the four independent variables have significant influenceto DER and other independence variables have no significant influence to DER. Profitability hassignificant positive influence toward debt, growth has significant negative influence toward debt,tangibility has significant positive influence toward debt, retained earning has significant negativeinfluence toward debt, but free cash flow and managerial ownership have no significant influencetoward debt.Key Words :Determinant, Agency Theory, Pecking Order Theory, Debt Policy,